2016
DOI: 10.1038/srep32385
|View full text |Cite
|
Sign up to set email alerts
|

Dairy and plant based food intakes are associated with altered faecal microbiota in 2 to 3 year old Australian children

Abstract: The first 1000 days (conception to 24 months) is when gut microbiota composition and eating patterns are established, and a critical period influencing lifelong health. The aim of this study is to examine the associations between food intakes and microbiota composition at the end of this period. Diet was quantified for 37 well-nourished Australian children aged between 2 to 3 years by using a food frequency questionnaire and 24 hr recalls. Both dairy and plant-based (fruit, vegetables, soy, pulses and nuts) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 56 publications
5
49
1
2
Order By: Relevance
“…Fruit intake in our study was higher than a previous Australian study, which reported only 28–45% meeting recommendations, depending on age . Studies have also shown an increase in the consumption of healthier foods, such as fruits, vegetables and grains, reported using food frequency questionnaires, which may explain the higher fibre intake in our study.…”
Section: Discussioncontrasting
confidence: 78%
“…Fruit intake in our study was higher than a previous Australian study, which reported only 28–45% meeting recommendations, depending on age . Studies have also shown an increase in the consumption of healthier foods, such as fruits, vegetables and grains, reported using food frequency questionnaires, which may explain the higher fibre intake in our study.…”
Section: Discussioncontrasting
confidence: 78%
“…To identify candidate sewage-associated Bacteroides markers, candidates were chosen by the criteria that they were Ͼ90% sensitive and 100% specific from Indicspecies results. To identify the probable source of these marker candidates (i.e., whether they are human derived or likely residents of the sewer pipes), we compared these marker candidate sequences with the National Center for Biotechnology Information (NCBI) nucleotide database and published V3V5 (69-71), V4V6 (72), V6 (73), and V6V8 (74) region human stool sequences using BLASTϩ. The most abundant Bacteroides in sewage was specific to sewage but did not appear to be of fecal origin.…”
Section: Methodsmentioning
confidence: 99%
“…This study utilises previously reported body composition data 8 for 36 children aged 2.24-3.12 years (female = 16) recruited from the ongoing Feeding Queensland Babies Study (FQBS). 9 The FQBS recruited first-time mothers whose children were born between June 2010 and April 2011 10 and involved mothers completing a prenatal questionnaire at 7-8 months of pregnancy followed by questionnaires at 2, 4, 6, 9 and 12 months of infant age. These questionnaires prospectively collected information on birthweight, infant growth and infant diet.…”
Section: Methodsmentioning
confidence: 99%